Interpersonal Communication Between Special Educational Needs Teachers and Parents of Special-needs Student During Covid-19 Pandemic - Sulistiyaningsih, Retno; Rohmah Hidayatul Qoyyimah, Nur; Syahidin Mubarok, Ali; Syahidin Mubarok, Ali (KnE Social Sciences, 2022)
The pandemic has had a significant impact on all sectors, especially on education which has a systemic impact. The changing pattern of teaching, learning, and the consequences endured are also a problem, especially in schools that administer inclusive education. This results in a changing pattern of communication between teachers, special-needs students, and parents. The study aims to illustrate the interpersonal communication dynamics inherent between a teacher and a parent as a central figure in the study of courage for special-needs students. The type of method used was a qualitative method with a case study approach. The study included five participants, three with details of special educational needs teachers and two for parents of special-needs students. The study was conducted in a data search phase through observation, documentation, and interviews. To strengthen the results, the focus group discussion included the five participants directly. For data analysis Miles and Huberman method was applied, whereas for data credibility data triangulation was used. The results of this study indicated that interpersonal communication had a significant impact in helping special-needs students to learn and to survive the pandemic. Keywords: special educational needs teacher, interpersonal communication, parents of special needs students